Los insectos escama (Hemiptera: Sternorrhyncha: Coccoidea) presentes sobre plantas medicinales - Mestre Novoa, N.=700 1 Veitia Rubio, M.; Hodges, G.S.
(Es, En)
Ilus., 39 ref.
Keywords: COCCOIDEA; INSECTOS; PLANTAS MEDICINALES; PLANTAS HUESPEDES; CUBA; INSECTOS ESCAMAS